Interhospital network system using the Worldwide Web and the Common Gateway Interface...Proccedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston TX, May 6-9, 1999 - Oka A; Harima Y; Nakano Y; Tanaka Y; Watanabe A; Kihara H; Sawada S (Journal of Digital Imaging)
We constructed an interhospital network system using the worldwide web (WWW) and the Common Gateway Interface (CGI). Original clinical images are digitized and stored as a database for educational and research purposes. Personal computers (PCs) are available for data treatment and browsing. Our system is simple, as digitized images are stored into a Unix server machine. Images of important and interesting clinical cases are selected and registered into the image database using CGI. The main image format is 8- or 12-bit Joint Photographic Experts Group (JPEG) image. Original clinical images are finally stored in CD-ROM using a CD recorder. The image viewer can browse all of the images for one case at once as thumbnail pictures; image quality can be selected depending on the user's purpose. Using the network system, clinical images of interesting cases can be rapidly transmitted and discussed with other related hospitals. Data transmission from relational hospitals takes 1 to 2 minutes per 500 Kbyte of data. More distant hospitals (e.g., Rakusai Hospital, Kyoto) takes 1 minute more. The mean number of accesses our image database in a recent 3-month period was 470. There is a total about 200 cases in our image database, acquired over the past 2 years. Our system is useful for communication and image treatment between hospitals and we will describe the elements of our system and image database. Copyright (c) 1999 by W.B. Saunders Company